Multi-omics study of the anti-colorectal cancer mechanisms of formononetin in Hedysari Radix - Rao, Jun; Wang, Xing; Chen, Tanxiu; Mo, Mingzi; Xu, Conglong; Chang, So-Yi; Hsu, Ssu-Wei; Han, Xiaoqun; Chen, Ching-Hsien; Zheng, Zhi (Frontiers in Pharmacology, 2026)
BackgroundHedysari Radix (HR), commonly known as Hong-Qi in Chinese, is a traditional Chinese herbal medicine recognized for possessing anti-inflammatory and anti-tumor properties. While the polysaccharides in HR have been extensively studied, other HR metabolites and their potential anti-tumor properties remain largely unknown.MethodsWe employed a multi-omics strategy integrating metabolomics, network analysis, proteomics, phosphoproteomics, and molecular docking to identify HR metabolites with anti-colorectal cancer (CRC) property and investigate underlying mechanisms.ResultsUsing mass spectrometry-based metabolomics, we identified 1,292 metabolites across eight processed HR products. Key metabolites including medicarpin, formononetin, naringenin, and quercetin were validated via the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP). Notably, formononetin-derived metabolites were significantly enriched during HR processing. The metabolite-metabolite correlation analysis revealed key compounds such as flavonoids and formononetin. Subsequent network analysis combined with label-free data-independent acquisition (DIA) proteomics and phosphoproteomics in colon cancer cells identified 194 potential targets, 291 differentially expressed proteins, and 1,535 phosphorylated proteins that were regulated by formononetin. Cell-surface enzymes carbonic anhydrase IX (CA9) and membrane metalloendopeptidase (MME) were consistently identified in different analyses as key targets, and molecular docking results confirmed their strong binding to formononetin. Bioinformatics analyses further revealed significant enrichment of cancer-associated pathways, including PI3K-Akt, Hippo, HIF-1 signaling, and cholesterol metabolism upon formononetin treatment.ConclusionThe findings provide novel insights into the HR metabolome and reveal the multi-targeting roles of formononetin in CRC development, laying the foundation for developing new CRC therapeutic strategies.